Bleeding Complications After Percutaneous Native Kidney Biopsy: Results From the Boston Kidney Biopsy Cohort - Ragnar Palsson; Samuel A.P. Short; Zoe A. Kibbelaar; Afolarin Amodu; Isaac E. Stillman; Helmut G. Rennke; Gearoid M. McMahon; Sushrut S. Waikar (Kidney International Reports, 2020)
Background: The major risk of kidney biopsy is severe bleeding. Numerous risk factors for bleeding after biopsy have been reported, but findings have been inconsistent. Methods: We retrospectively reviewed medical records of adult patients enrolled in a native kidney biopsy cohort study to identify major bleeding events (red blood cell [RBC] transfusions, invasive procedures, kidney loss, or death). We used logistic and linear regression models to identify characteristics associated with postbiopsy RBC transfusions and decline in hemoglobin within a week after the procedure. Results: Major bleeding events occurred in 28 of 644 (4.3%) patients (28 required an RBC transfusion, 4 underwent angiographic intervention, and 1 had open surgery to control bleeding). No patient lost a kidney or died because of the biopsy. Postbiopsy RBC transfusion risk was driven by the baseline hemoglobin level (odds ratio [OR] 13.6; 95% confidence interval [CI] 5.4–34.1 for hemoglobin <10 vs. ≥10 g/dl). After adjusting for hemoglobin, no other patient characteristics were independently associated with RBC transfusions. Female sex (β = 0.18; 95% CI: 0.04–0.32), estimated glomerular filtration rate (eGFR) <30 ml/min per 1.73 m2 (β = 0.32; 95% CI: 0.14–0.49), and baseline hemoglobin (β = 0.09; 95% CI: 0.05–0.13, per g/dl increase) were independently associated with a larger drop in hemoglobin. Histopathologic lesions were not independently associated with major bleeding after biopsy. Conclusion: Biopsies were generally well tolerated. Baseline hemoglobin was the dominant risk factor for RBC transfusions, but female sex and eGFR <30 ml/min per 1.73 m2 were also associated with a larger decline in hemoglobin after the procedure. Keywords: biopsy, bleeding, blood transfusions, kidney diseases, risk factors